Multi-Walled Carbon Nanotubes as Efficient Sorbent for the Solid Bar Microextraction of non-Steroidal Anti-Inflammatory Drugs from Human Urine Samples - AL-Hashimi, Nabil N.; Aleih, Haneen A.; Fasfous, Ismail I.; AlKhatib, Hatim S. (Current Pharmaceutical Analysis, 2018)
Background: The determination of NSAIDs (ketoprofen, diclofenac, and ibuprofen) in urine samples provides useful information for assessing their safety, therapeutic effect, and their mechanism of action. Urine samples are characterized by their complexity and low concentration of the target analytes, which make their direct analysis difficult. In this work, the potential of multi-walled carbon nanotubes (MWCNTs) as Solid Bar Microextraction (SBME) adsorbents for extraction and preconcentration of selected drugs from urine samples have been investigated. Methods: Five SBME devices (contains 10 mg of MWCNTs) were placed in 30 mL of adjusted pH 2 water samples and stirred for 40 minutes. After finishing the extraction, the devices were ultrasonicated in 250 μL of methanol for 5 min to desorb the selected drugs and analyzed using HPLC-DAD. Results: The analytical performance of the whole method was evaluated in water samples. Limits of detection and quantitation were in the ranges of (0.36- 0.52) and (1.2- 1.7) μg L-1, respectively, and the Relative Standard Deviation (RSD) < 5.7% over a concentration range of 5-100 μg L-1. Application: The proposed method was successfully applied to the analysis of selected drugs in spiked human urine samples. The absolute recovery obtained by spiking the urine samples at three concentration levels: 5, 50 and 100 μg L-1 of selected NSAIDs were from 48.8% to 53.5%. Conclusion: The proposed SBME using MWCNT as a sorbent material can be a useful alternative sample preparation technique for the routine determination of NSAIDs in urine samples at therapeutic levels with very simple sample pretreatment. Furthermore, the application of the developed SBME method might be extended to study the determination of selected non-steroidal anti-inflammatory drugs in veterinary urine samples.
Keywords: solid bar microextraction